2014
DOI: 10.1016/j.epsc.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A human case study demonstrating the safety and effectiveness of laparoscopic surgical glue injection hernioplasty for pediatric indirect inguinal hernia

Abstract: a b s t r a c tThe purpose of this pediatric case report was to provide clinical evidence supporting the safety and effectiveness of laparoscopic surgical glue injection hernioplasty (LSGIH) in humans for indirect inguinal hernia repair. We performed LSGIH on a female newborn for a right indirect inguinal hernia that was incidentally discovered during a laparoscopic right salphingo-oophorectomy for prenatal right ovarian cyst torsion. Under laparoscopic control, the internal ring was closed by injection of His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In previous studies, Kato and Ayman reported that the use of glue was effective in the repair of inguinal hernia, with no recurrence on long-term follow-up, no damage to spermatic cord structures, and no clear impact on fertility [18,41]. Similarly, in our study, the glue was partially absorbed after LGH, which was confirmed by a second surgery due to ovarian torsion, where the glue injection site remained completely closed, without any intraperitoneal organ adhesion [42]. In contrast, Miyano et al reported concerns on the increased risk of intestinal obstruction by adhesive syndrome, hernia recurrence, postoperative hydrocele, and long-term carcinogenesis [24].…”
Section: Discussionsupporting
confidence: 84%
“…In previous studies, Kato and Ayman reported that the use of glue was effective in the repair of inguinal hernia, with no recurrence on long-term follow-up, no damage to spermatic cord structures, and no clear impact on fertility [18,41]. Similarly, in our study, the glue was partially absorbed after LGH, which was confirmed by a second surgery due to ovarian torsion, where the glue injection site remained completely closed, without any intraperitoneal organ adhesion [42]. In contrast, Miyano et al reported concerns on the increased risk of intestinal obstruction by adhesive syndrome, hernia recurrence, postoperative hydrocele, and long-term carcinogenesis [24].…”
Section: Discussionsupporting
confidence: 84%
“…6 Despite these concerns, Park et al reported very promising results with laparoscopic surgical glue injection hernioplasty in children. 18,19 Their method required only one working port and one camera port and b-CNA glue was adopted to close the defect after the mesothelial layer surrounding the internal inguinal ring was electrically cauterized. The main limitation of this study was that it did not include male patients to avoid potential damage to the vas deferens.…”
Section: Discussionmentioning
confidence: 99%